Differential effects of acute exercise on emotional memory in men and women - Nakamura, Miyuki; Kawata, Yujiro; Hirosawa, Masataka; Ota, Tsuneyoshi; Shibata, Nobuto (Frontiers in Sports and Active Living, 2023)
Exercise may change emotional memory, which is associated with the induction of mental disorders such as depression and anxiety. This effect of exercise may be influenced by exercise-induced cortisol release. Depending on sex, cortisol exerts differential effects on emotional memory consolidation. However, whether acute exercise and exercise-induced cortisol release have sex-dependent effects on emotional memory has not been established. Therefore, first, we aimed to determine the effects of acute exercise on emotional memory, separately for men and women, in a within-subjects design. Second, we aimed to examine whether the effects of acute exercise on emotional memory are related to the effects of exercise-induced cortisol release, separately for men and women. Sixteen healthy men and 15 healthy women were presented with positive and negative emotional images, followed by either rest or a vigorous-intensity cycling exercise condition using a within-subjects design on separate days. Salivary cortisol was measured before presenting the emotional images presentation and 20 minutes after each intervention. Emotional memory was assessed two days later. Vigorous-intensity exercise decreased emotional memory in women, whereas there was no change in men after rest or exercise. Cortisol levels increased after exercise intervention in both men and women, although there was no association between cortisol levels and emotional memory. These findings demonstrate that the effect of a single bout of vigorous-intensity exercise on emotional memory differs between men and women and is associated with decreased emotional memory in women.